Evaluation of Health Promotion Program for the Prevention of Epidemics at Primary Health Care Centers in Baghdad City: Comparative Study - Mansur, Mohammed; Khalifa, Muhammed (Iraqi National Journal of Nursing Specialties, 2020)
Objective(s): To evaluate and compare between Health Promotion Program for the Prevention of Epidemics at Primary Health Care Centers in Baghdad City.Methodology: A descriptive study, using the evaluation and comparative approaches, is conducted to evaluate health promotion program for the prevention of epidemics at primary health care centers in baghdad city from October 15th  2019 through March 1st 2020. A purposive, non-probability, sample of (42) health promotion unit officers were recruited from the same number of primary health care centers which were divided into (14) main, (14) sub and (14) family medicine primary health care centers in Baghdad City. Interview schedule instrument is constructed for the purpose of the study. Such instrument is comprised of (2) parts; Demographic information sheet and evaluation of health promotion program. Content validity and internal consistency reliability are determined  the study instrument through pilot study. Data were collected through the use of the study instrument and the application of the interview technique as means of data collection. Data were analyzed through the application of descriptive statistical data analysis approach of frequency, percentage, total scores, ranges and mean and inferential statistical data analysis approach of analysis of variance.Results: The study results indicate that the family medicine primary health care centers have implemented the health promotion program more sufficiently and effectively than main and sub primary health care centers.Recommendations: The present study recommends that periodic and regular evaluation of the health promotion program is required at health directorates, health care sectors and primary health care centers for the determination of monitoring its utility. Further studies can be carried out on a larger sample size of primary health care centers and a nationwide scale.